Thinking and speaking in two languages - Pavlenko, Aneta (Bilingual education&bilingualism, 2011)
Until recently, the history of debates about language and thought has been a history of thinking of language in the singular. The purpose of this volume is to reverse this trend and to begin unlocking the mysteries surrounding thinking and speaking in bi- and multilingual speakers. If languages influence the way we think, what happens to those who speak more than one language? And if they do not, how can we explain the difficulties second language learners experience in mapping new words and structures onto real-world referents? The contributors to this volume put forth a novel approach to sec